Doxorubicin–Trabectedin with Trabectedin Maintenance in Leiomyosarcoma - Pautier, Patricia; Italiano, Antoine; Piperno-Neumann, Sophie; Chevreau, Christine; Penel, Nicolas; Firmin, Nelly; Boudou-Rouquette, Pascaline; Bertucci, François; Lebrun-Ly, Valérie; Ray-Coquard, Isabelle; Kalbacher, Elsa; Bompas, Emmanuelle; et al. (The New England journal of medicine, 2024)
Among patients with leiomyosarcoma, a combination of doxorubicin and trabectedin with prolonged trabectedin maintenance therapy led to longer overall survival than doxorubicin alone (median, 33 vs. 24 months).